2012
DOI: 10.1016/j.ajpath.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin Transporter Modulates Wound Healing in Diabetes by Regulating Prostaglandin-Induced Angiogenesis

Abstract: Prostaglandin transporter (PGT) mediates prostaglandin (PG) catabolism and PG signal termination. The prostanoid PGE(2), which induces angiogenesis and vasodilation, is diminished in diabetic skin, suggesting that PGT up-regulation could be important in wound healing deficiency, typified by diabetic foot ulcer. We hypothesized that up-regulation of PGT in hyperglycemia could contribute to weakened PGE(2) signaling, leading to impaired angiogenesis and wound healing. In human dermal microvascular endothelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 59 publications
1
61
3
Order By: Relevance
“…We did not detect any differences in the production of prostacyclin (another prostanoid that exerts immunoregulatory properties) or PGE 2 metabolites in the skin of diabetic mice infected with MRSA. These data contrast with previous reports that showed that hyperglycemia enhances prostaglandin degradation by increasing the expression and activity of PGE 2 transporter, leading to diminished PGE 2 levels and angiogenic signaling in diabetic skin (15). The reasons for such discrepancies are unknown, but it could be due to differences in animal models, cells involved in the inflammatory response during angiogenesis, and infection.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We did not detect any differences in the production of prostacyclin (another prostanoid that exerts immunoregulatory properties) or PGE 2 metabolites in the skin of diabetic mice infected with MRSA. These data contrast with previous reports that showed that hyperglycemia enhances prostaglandin degradation by increasing the expression and activity of PGE 2 transporter, leading to diminished PGE 2 levels and angiogenic signaling in diabetic skin (15). The reasons for such discrepancies are unknown, but it could be due to differences in animal models, cells involved in the inflammatory response during angiogenesis, and infection.…”
Section: Discussioncontrasting
confidence: 99%
“…As well, during wound healing, diabetic mouse skin exhibits a decreased capacity to produce PGE 2 (15). Moreover, diminished production of COX products of arachidonic acid metabolism have been described as an abnormality of polymorphonuclear leukocytes in diabetes (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the environment of chronic inflammation, PGT is expressed at lower levels than in normal tissue (53). It is unclear whether the reduction of PGT expression causes chronic inflammation by decreasing PGE 2 clearance, or is a result of the sustained pro-inflammatory environment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that PGE 2 regulates angiogenesis (17,18). Its receptor is EP3 (19,20), and suppression of cAMP is caused by EP3 activation (21,22).…”
mentioning
confidence: 99%